Wandering in the Word-Woods: Some Thoughts on the Arrangement of Dictionaries - Poteet, Lewis J. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
Following my early experience of word-books, I chose the A-Z arrangement for entries in the small dictionaries I have written - The South Shore Phrase Books (three), The Far Eastern Townships Phrase Book, and The Hockey Phrase Book. However, Connie Eble’s College Slang 101 (1989) is arranged topically, using a form which led me to alter radically the format for Parlons Hockey Talk, the new attempt to record the hockey lexicon in both English and French. The hidden assumptions and unwritten messages behind the A-Z arrangement tend to perpetuate the popular assumptions that dictionaries claim a comprehensiveness which most lexicographers have renounced. Using alternative formats harmonizes with the primacy of vowel sounds in making linguistic atlases as well as acknowledging the concept and utility of ‘keywords’ in speech communities. Dictionaries and word-books need to acknowledge more explicitly their function as guides to the pathways among language units in a larger linguistic reality than they may ever map completely.